Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2478/cait-2021-0028
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Proxy Re-Signature Schemes for Translating One Type of Signature to Another

Abstract: Proxy Re-Signature (PRS) complements well-established digital signature service. Blaze-Bleumer-Strauss discussed PRS in 1998 for translating a signature on a message from Alice into a signature from Bob on the same message at semi-trusted proxy which does not learn any signing-key and cannot produce new valid signature on new message for Alice or Bob. PRS has been largely ignored since then but it has spurred considerable research interest recently for sharing web-certificates, forming weak-group signatures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Our finding reported the prevalence of overweight was 60% and obese was 40% and it can relate to the unhealthy and sedentary lifestyle among the students. Chaudhari et al [11] reported a positive correlation between blood sugar levels and obesity. Increase in random blood glucose level (Figure 1) was observed in the obese II groups by 101.4% when compared to the control.…”
Section: Bmi and Blood Glucosementioning
confidence: 98%
“…Our finding reported the prevalence of overweight was 60% and obese was 40% and it can relate to the unhealthy and sedentary lifestyle among the students. Chaudhari et al [11] reported a positive correlation between blood sugar levels and obesity. Increase in random blood glucose level (Figure 1) was observed in the obese II groups by 101.4% when compared to the control.…”
Section: Bmi and Blood Glucosementioning
confidence: 98%
“…Lv et al [Lv et~al., 2020] introduced a threshold bidirectional PRS scheme without using RO. Very recently, Chaudhari et al [Chaudhari et~al., 2021] gave a survey on PRS scheme.…”
Section: Related Work On Proxy Re-signature Schemementioning
confidence: 99%